Howard Watkins' Retirement from Fresno-Merced Counties Legal Services Dinner at Yen Ching Restaurant - Watkins, Howard::::::::: (1985)
?, Carolyn Phillips, Kurt Hoff, Michael Kanz and Doris Burnes Chinese writings on the wall